Overview of a Gas Turbine Blades Power Plant - M., Wurood Asaad; khenyab, Ali yousif; Shaker, Lina M.; Kdhim, Ruaa Hatem (Al-Salam Journal for Engineering and Technology, 2023)
Power plants that employ turbine blades to generate electricity usually need them to have certain qualities, like high strength, fatigue and corrosion resistance, and temperature tolerance. Super alloys and ceramic composites are common materials used in their construction. Defects or imperfections that might impair the performance and lifetime of turbine blades are a typical issue in their production. Casting flaws, material inclusions, and inadequate cooling during manufacturing are a few examples of these faults. Power plants use strict inspection procedures and quality control measures to reduce these problems and guarantee the dependability of their turbine blades. Improvements in material composition and design are usually required when changing the materials used in turbine blades to boost their effectiveness and performance. Depending on the particular use and intended result, turbine blades can undergo a variety of alterations. Advanced alloy material modifications, coatings, ceramic matrix composites (CMCs), airfoil design optimization, cooling technologies, and tip modifications are a few examples of typical modifications. It's important to note that the specific modifications applied to turbine blades can vary widely depending on the type of turbine (gas, steam, wind, etc.), the operating conditions, and the goals of the modification.